Indigenous cosmic caretaking and the future of space exploration - Karlie Alinta Noon (Centre for International Governance Innovation (CIGI), 2024)
Cosmic caretaking highlights the importance of fostering meaningful collaboration grounded in the principle of sustainable environment caretaking. The findings of this paper emphasize the significance of preserving and protecting celestial environments through Indigenous led astro-environmentalism and conservation efforts. It underscores the need for respectful relationships between space agencies, research institutions and Indigenous communities, supporting a culture of co-creation and co‑management to address environmental impacts, ethical activities and heritage preservation.
Keywords: 330